2007
DOI: 10.1097/iae.0b013e31802eff83
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab (Avastin) for Central and Hemicentral Retinal Vein Occlusions

Abstract: Intravitreal bevacizumab injections of 2.0 mg at 12-week intervals were well tolerated and were associated with short-term BCVA stabilization or improvement and favorable macular changes in all patients with ischemic RVO and associated macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(100 citation statements)
references
References 36 publications
4
92
2
2
Order By: Relevance
“…In our study, the dose of 1.25 mg of bevacizumab was similar to several previous studies (8,1013,21,22) using the same treatment modality ex cept for that used in the study published in 2007 which used 2.5 mg of bevacizumab with similar favorable results (20) . The favorable effect of treatment observed in our study is also in agreement with the po sitive results obtained by others authors which used repeated 2.0 mg bevacizumab injections at three months interval in patients with central and hemicentral retinal vein occlusion (27) . While it seems clear that IVB injection has a shortterm beneficial effect, it is also clear from several studies that recurrence of ME is rather frequent (8,11,12) , and very often repeated injections are neces sary in patients with retinal vein occlusion.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the dose of 1.25 mg of bevacizumab was similar to several previous studies (8,1013,21,22) using the same treatment modality ex cept for that used in the study published in 2007 which used 2.5 mg of bevacizumab with similar favorable results (20) . The favorable effect of treatment observed in our study is also in agreement with the po sitive results obtained by others authors which used repeated 2.0 mg bevacizumab injections at three months interval in patients with central and hemicentral retinal vein occlusion (27) . While it seems clear that IVB injection has a shortterm beneficial effect, it is also clear from several studies that recurrence of ME is rather frequent (8,11,12) , and very often repeated injections are neces sary in patients with retinal vein occlusion.…”
Section: Discussionsupporting
confidence: 93%
“…They inhibit the release of VEGF, contribute to the integrity of the inner blood-retinal barrier, reduce extravasation from leaking blood vessels, and have beneficial effect in the prevention and treatment of macular oedema. 20,26,27 The safety of intravitreal bevacizumab has been confirmed by previous animal studies and human trials, 28,29 and intravitreal injection of bevacizumab has recently been reported to be effective in macular oedema of various etiologies. 20,[30][31][32][33] Results of our study suggest that intravitreal bevacizumab injection appears to be effective in the primary treatment of DME.…”
Section: Resultsmentioning
confidence: 79%
“…16 Although intravitreal injection of bevacizumab has not received FDA approval, bevacizumab has been widely used off-label to treat VEGF-mediated ocular conditions such as choroidal neovascularization secondary to age-related macular degeneration, diabetic macular edema, CRVO-associated macular edema and as an adjunctive agent in glaucoma surgery. [17][18][19][20][21] The outcomes of off-label treatment of NVG with intravitreal bevacizumab have been reported. [22][23][24][25][26][27][28][29][30] We have previously published a retrospective interventional case series of NVG eyes describing the natural history of NVG treated with intravitreal bevacizumab.…”
Section: Introductionmentioning
confidence: 99%